Employment opportunities as perceived by selected UPV College of Management (CM) graduates - Artuz, May Ann B.; Beriana, Charlene A.; Desales, Aimee D.; Esparagosa, Freda; Omayao, Rhona A.
This study aims to find out the employment opportunities for the graduates of UP College of Management. The chosen respondents are the graduates of the academic years 1998-2002. In this study, we were able to identify the factors that affect the graduates in their search for jobs. Grades are not the primary consideration in employment. The independent variables in this study are the college graduates and career movement, which include job performance, while promotion is the dependent variable. Other factors that are considered by companies in hiring are skills, school graduated, and one's personality. The time lag or the period after graduation until finding the first job is diminutive.